2011
DOI: 10.1111/j.1445-2197.2010.05632.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose computed tomography versus plain abdominal radiography in the investigation of an acute abdomen

Abstract: LDCT demonstrates a superior diagnostic yield over AR and reduces the number of subsequent imaging tests for a minimal cost in radiation exposure. However, there is no difference in the overall hospital LOS between the two imaging strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…Not all studies provided data for evaluation of both overall performance and bowel obstruction, which explains a lower number of studies in each of these figures. In a randomized controlled trial by Nguyen et al [12] for the diagnosis of bowel obstruction, a sensitivity of 82 % was reported for low-dose CT and 62 % for abdominal radiography, with a specificity of 93 % and 92 %, respectively.…”
Section: Diagnostic Performancementioning
confidence: 94%
See 1 more Smart Citation
“…Not all studies provided data for evaluation of both overall performance and bowel obstruction, which explains a lower number of studies in each of these figures. In a randomized controlled trial by Nguyen et al [12] for the diagnosis of bowel obstruction, a sensitivity of 82 % was reported for low-dose CT and 62 % for abdominal radiography, with a specificity of 93 % and 92 %, respectively.…”
Section: Diagnostic Performancementioning
confidence: 94%
“…2). One of these was later excluded from the numerical analysis because of insufficient data [12] despite twice trying to contact the authors. The study characteristics are shown in Table 2.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…[567] It can also frequently identify the exact site of gastrointestinal perforation when present and diagnose a wide range of other intra-abdominal pathology. [89101112131415] The accuracy of CT for identifying the site of perforation ranges from approximately 70% to 90%. [56] The additional information gained by CT may be useful in either directing or avoiding surgery in patients with pneumoperitoneum on plain X-ray.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al. described the performance of low‐dose CT of the abdomen in comparison to abdominal radiographs 8. The results are promising but despite technological advances, the radiation dose remains at 2–3 mSv.…”
mentioning
confidence: 99%
“…Nguyen et al described the performance of low-dose CT of the abdomen in comparison to abdominal radiographs. 8 The results are promising but despite technological advances, the radiation dose remains at 2-3 mSv. The advantage of CT is that it serves a one-stop imaging modality for most of the causes of the acute abdomen, including rare abnormalities.…”
mentioning
confidence: 99%